Telocytes in ileum of the Chinese giant salamander: ultrastructural evidence. Issue 3 (25th January 2016) - Zhang, Hui; Zhong, Shengwei; Ge, Tingting; Peng, Shasha; Yu, Pengcheng; Zhou, Zuohong; Guo, Xiaoquan
Abstract: Telocytes (TCs) and their telopodes (Tps) have been found in various organs of many mammals, including in lower animals. However, knowledge of TCs in lower animals is still very limited. This study identified TCs and their Tps in the ileum of the Chinese giant salamander, Andrias davidianus (Amphibia: Caudata), by transmission electron microscopy. The TCs/Tps were found near epithelial cells, glandular cells and unmyelinated nerve fibres. Moreover, exosomes were also found to be present in between TCs/Tps and these cells.